Chemical Characterization, Nutritional and Bioactive Properties of Physalis peruviana Fruit from High Areas of the Atacama Desert - Patricio Muñoz; Felipe Parra; Mario J. Simirgiotis; Germán F. Sepúlveda Chavera; Claudio Parra (Foods, 2021)
Physalis peruviana L. belongs to the Solanaceae family and produces a spherical fruit used to treat various diseases. However, the chemical composition, nutritional characterization, and bioactive properties of the P. peruviana growing in the Andean region of the Atacama Desert have not been conducted so far. The results showed clear differences in the nutritional and bioactive characteristics of the fruits grown in arid environmental conditions, which were comparable to those from countries with a production tradition. The fruits studied showed a higher Ca, Cu, Mn, P, and Zn content and bioactive compounds such as flavonoids and tannins than those reported in the literature. UHPLC was performed to determine the main phenols. Gallic acid was identified as the predominant phenolic compound in this species (303.63 mg/100 g FW), of which to our knowledge no previous study has reported similar concentrations in this species. Moreover, Cape gooseberry extract has antioxidant and antimicrobial activity against Gram-positive and Gram-negative bacteria. Pseudomonas syringae (MIC 0.313 mg/mL and MBC 1.25 mg/mL) was the most susceptible bacterium. Meanwhile, Erwinia rhapontici was the most resistant bacterium (MIC and MIB 5.00 mg/mL). Furthermore, it was found to inhibit α-amylase activity with an IC50 value (39.28 µg/mL) similar to that of acarbose (35.74 µg/mL). These results expand the knowledge of the species cultivated in arid environmental conditions and suggest an alternative for the potential use of this fruit to manage chronic diseases such as diabetes.